Two new species of the apterous Carventinae genus Comorocoris Heiss, 1985 from Madagascar (Hemiptera: Heteroptera: Aradidae) - Heiss, Ernst; Baňař, Petr; Rahanitriniaina, Lalao Sahondra (Zootaxa, 2012)
The monobasic genus Comorocoris Heiss, 1985 was erected for the peculiar apterous species C. testudiformis fromMoheli Island [= Mwali] of the Comoro Archipelago. Recent forest litter sifting in Madagascar unexpectedly brought to light two new species belonging to this genus which are described and illustrated. A key to the three species is given.